2018
DOI: 10.1080/21641846.2018.1426371
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of lymphocyte subsets with clinical outcomes in chronic fatigue syndrome

Abstract: Background: Chronic fatigue syndrome (CFS) is characterized by prolonged fatigue and other physical and neurocognitive symptoms. Some studies suggest that CFS is accompanied by disruptions in the number and function of various lymphocytes. However, it is not clear which lymphocytes might influence CFS symptoms. Purpose: To determine if patient reported fatigue symptoms and physical functioning scores significantly changed across time with lymphocyte counts as evidence of a relation among chronic fatigue symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Emphasis has been placed on post-exertional malaise, the characteristic exacerbation of symptoms following minimal effort, as a distinguishing feature of ME/CFS ( Carruthers et al , 2003 ). Biomarker studies suggest roles for cytokines ( Hornig et al , 2016 ), reduced natural killer cell activity ( Caligiuri et al , 1987 ; Mehalick et al , 2018 ), microRNAs ( Baraniuk and Shivapurkar, 2017 ), metabolomics ( Armstrong et al , 2014 ), gut microbiome ( Du Preez et al , 2018 ), neuroinflammation with microglial activation ( Nakatomi et al , 2014 ) and brainstem connectivity and myelination changes ( Barnden et al , 2016 , 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emphasis has been placed on post-exertional malaise, the characteristic exacerbation of symptoms following minimal effort, as a distinguishing feature of ME/CFS ( Carruthers et al , 2003 ). Biomarker studies suggest roles for cytokines ( Hornig et al , 2016 ), reduced natural killer cell activity ( Caligiuri et al , 1987 ; Mehalick et al , 2018 ), microRNAs ( Baraniuk and Shivapurkar, 2017 ), metabolomics ( Armstrong et al , 2014 ), gut microbiome ( Du Preez et al , 2018 ), neuroinflammation with microglial activation ( Nakatomi et al , 2014 ) and brainstem connectivity and myelination changes ( Barnden et al , 2016 , 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of family members without ME/CFS as controls in the present report resulted in the rapid identification of unsuitable diagnostic ADCC biomarkers et al observed in 1987 that CFS patients have low NK activity [28]. Studies followed that reported low NK function (reviewed [29], also [30][31][32][33]), NK phenotypes consistent with lower NK cell function (e.g., low perforin [34]; low granzyme B [33]; lower frequency of the more cytotoxic CD56dim NK cells [35], and low ERK1/2 kinase [36]), and fewer blood NK cells in patients during CFS disease episodes [37]. In contrast, a recent Scandinavian study with large numbers of ME/CFS patients indicates that many CFS patients have normal NK activity and that low NK activity is unsuitable as a biomarker for this disease [38].…”
Section: Introductionmentioning
confidence: 99%